An evidence-based health and safety analysis in megaproject management - Maiti, Saikat; de Almeida, Nuno Marques (Technium Social Sciences Journal, 2023)
Despite of the remarkable improvement in terms of health and safety in the construction sector through the implementation of a variety of regulations across the world, till health and safety issues are increasing rapidly. Meanwhile, Health and safety issues on construction sites are still significant in terms of a consistent high number of work-related illnesses and injuries in the construction to recent statistics from the Health and Safety Executive (HSE). Interest is growing on to support the designer to take care of health and safety from the design stage in building construction with regards to techno-commercial aspect. This is a fact that, design influences to a great extent the nature of these hazards that are in building construction. Meaning that the hazards need to be eliminated or minimized at the designing stage. “Safe design”denotesthat in the hazard be identified and risks are assessed early in the design process to minimize or eliminate the injury risks during the lifecycle of the project. Based on an extensive review of the causes of work-related illnesses and injuries in building construction including mining production, this paper identifies a set of technical issues relating to building design. By presenting a new evidence-based health and safety analysis, abbreviated to EHSA approach for designers (architects and engineers) to use towards safer design for construction thereby, reducing work-related injuries and illnesses on site and decrease the economic losses. The research into EHSA is intended to evaluate an innovative way to facilitate evidence-based learning in building design with the collection and use of data and information accumulated from professional knowledge about fatalities and accidents along with best practices and innovations in field of health safety management that have proven to be effective for the construction industry. Through an experimental case study, this conference paper will demonstrate how the EHSA approach can help in effectively supporting health and safety improvement at the design stage. The paper is anticipated to contribute significantly to existing body of knowledge by introducing a new framework in safer building design by providing an innovative approach with an evidence-based experimental case study to innovate future practice while also leveraging the findings for improvement in health and safety management.